Modulation of resistive states of oxide heterostructures - Oo, Win Shwe Sin (2019)
With the advancement of information and technology, the demand for the memory storage devices has increased. With Moore’s law slowing down in chip market or even possibly coming to an end in the near future, there is an urgent need to implement alternative storage devices to replace the conventional memories. Among emerging non-volatile memories, Resistive random access memories (RRAMs) show a promising future for the next generation of storage devices. However, extensive research is required to fully understand the resistive switching mechanism and the impact of the materials used. This research investigates the mechanism of filament formation, ion migrations, and electron behaviors by applying pulsed voltage and illumination. The first section of the paper observes the switching behavior of LAO/LNO sample by applying pulsed voltage whereas the second section of the paper explores the photo-response of ZnO thin film under different illumination of visible light range. The last section inspects the photoelectric gating effect on resistive switching patterns of lithium ionic liquid coated ZnO thin film by applying gate voltage in addition to the illumination. The results are analyzed and the challenges as well as the future work of the resistive switching technology are stated so as to provide an insight on improving RRAM storage devices which have the possibility of dominating the future of high-speed and low power storage devices.